Optimization of the incorporation of PCM-drywalls in lightweight steel-framed (LSF) temporary houses in the South of Portugal - Capela, Diogo António Almeida (2023)
Dissertação de Mestrado em Engenharia Mecânica apresentada à Faculdade de Ciências e Tecnologia